2016
DOI: 10.1249/mss.0000000000000838
|View full text |Cite
|
Sign up to set email alerts
|

Does Intervening in Childcare Settings Impact Fundamental Movement Skill Development?

Abstract: A childcare provider-led PA-based intervention increased the FMS in preschoolers, driven by the change in locomotor skills. The childcare environment may represent a viable public health approach for promoting motor skill development to support future engagement in PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 25 publications
7
85
0
3
Order By: Relevance
“…Two school-based interventions, which focused on sports, provided improvements in some FMS skills but in general, the overall improvements in these studies were small compared to the present study (Lai et al, 2014, Barnett et al, 2009, Salmon et al, 2008). However, recent interventions that utilised active play to improve FMS have shown improvements in pre-school aged children and are more consistent with findings in the present study (Jones et al, 2011, Adamo et al, 2016). The mean GMQ score at baseline in our study was 83.2 (18.9th percentile) and significantly improved to 93.3 (36.1st percentile) in the intervention group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Two school-based interventions, which focused on sports, provided improvements in some FMS skills but in general, the overall improvements in these studies were small compared to the present study (Lai et al, 2014, Barnett et al, 2009, Salmon et al, 2008). However, recent interventions that utilised active play to improve FMS have shown improvements in pre-school aged children and are more consistent with findings in the present study (Jones et al, 2011, Adamo et al, 2016). The mean GMQ score at baseline in our study was 83.2 (18.9th percentile) and significantly improved to 93.3 (36.1st percentile) in the intervention group.…”
Section: Discussionsupporting
confidence: 91%
“…Key to developing physical literacy and therefore increasing physical activity levels is creating an environment that fosters an enjoyment of physical activity from an early age while developing key movement skills. Evidence has suggested that active play achieves both enjoyment and development of FMS thus providing an evidence-based justification as to why active play was the type of physical activity selected for the intervention (Jones et al, 2011, Adamo et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Yet in a recent study, locomotor (but not object control skills) improved over a 6-month intervention which demonstrated that a brief childcare center-based intervention can improve at least some FMS. 32 Based on the results of our study and speculating more, it is possible that in Finnish day care, more attention is paid to the type of physical activities children engage in and the context, for example playing outside, rather than the amount of PA. For example, in a recent Finnish study, children who were more physically active outdoors scored higher in six measured motor skills, but the PA was not significantly associated with total motor skills. 33 Indeed, in the study region, outdoor day care is becoming increasingly popular 34 and that might have an influence on motor skills.…”
Section: Discussionmentioning
confidence: 87%
“…Sample size estimates are based on the mean improvement in fundamental motor skills from results of a similar study by Adamo et al [45]. This study was a recently published randomised cluster trial that used a childcare provider led physical activity program designed for preschool children to improve fundamental motor skills.…”
Section: Sample Sizementioning
confidence: 99%